EFFECTS OF HABITAT QUALITY ON ABUNDANCE AND DISTRIBUTION OF OLIVE BABOON Papio anubis IN YANKARI GAME RESERVE - A, Malangale,; S. A, Manu,; J. I, Abalaka,; E. N, Gajere,; S. K, Dauda, (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
This study determined the abundance, density and distribution of Olive Baboon (Papio anubis) in relation to habitat quality in the Yankari Game Reserve. The integration of remote sensing, GIS, and statistical analysis provides a good tool for Olive Baboon distribution mapping and determination of habitat quality using Normalized Difference Vegetation Index (NDVI) and micro climatic variables. Habitat quality of Olive Baboon was described via Normalized Difference Vegetation Index (NDVI) as a measure of vegetation primary productivity, distance from water source, temperature, relative humidity and habitat types. Olive Baboons were more abundant in the gallery forest (1211) than in the savannah (414). The distribution map generated from the sightings of Olive Baboons during this study also agrees with the abundance result, revealing higher concentration of Olive Baboons in the gallery forest than in the savannah. The most widely used index of habitat quality is the population density that a habitat can support at carrying capacity; a quality habitat can support high population density. Result from this study showed that gallery forest had a higher density of Olive Baboons (0.261 Olive Baboons/ha) than the savannah with a population density of 0.042 Olive Baboons/ha. Olive Baboons in the Yankari Game Reserve tend to select better quality habitat, characterized by water source, high relative humidity, suitable NDVI values (0.38) and suitable temperature.